2011
DOI: 10.3141/2229-06
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Clearance Time of Urban Traffic Accidents in Abu Dhabi, United Arab Emirates, with Hazard-Based Duration Modeling Method

Abstract: Traffic incidents generate adverse impacts in many areas, including traffic flow, air pollution, fuel consumption, and secondary crashes; therefore, it is vital for traffic incident responders and operators to know how they can improve the efficiency of traffic incident management. This paper presents the results of an investigation of the effects of traffic accident characteristics on accident clearance time using fully parametric hazard-based duration models with emphasis on the accelerated failure time metr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 17 publications
2
36
1
1
Order By: Relevance
“…Some studies showed that the distributions are different [4,6,7,[19][20][21][23][24][25]. The differences in the findings that were described may have resulted from several factors, including small sample sizes (several hundred accident records), poor quality of accident data, differences in the factors that affected accident duration, and differences among the countries from which the data was obtained.…”
Section: Literature Reviewmentioning
confidence: 84%
See 1 more Smart Citation
“…Some studies showed that the distributions are different [4,6,7,[19][20][21][23][24][25]. The differences in the findings that were described may have resulted from several factors, including small sample sizes (several hundred accident records), poor quality of accident data, differences in the factors that affected accident duration, and differences among the countries from which the data was obtained.…”
Section: Literature Reviewmentioning
confidence: 84%
“…An interesting result was observed with regard to the effect that occurred when a taxi was involved in the accident: the duration lengthened when a taxi was involved. Using accident clearance time data from the city of Abu Dhabi, Alkaabi et al [21] developed the Weibull AFT model (without gamma heterogeneity), which showed that accident clearance times were longer and involved more casualties and vehicles when accidents occurred during out-of-peak hours, during January and March, and under severe weather conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Typically, an incident is expected to be more likely to clear if it has continued for longer. This distinct feature of hazard-based duration models has inspired many studies to apply same method, but use different or mixture probability distributions that specify hazard functions or unobserved heterogeneity (Qi and Teng, 2008;Qi et al, 2009;Chung, 2010;Chung et al, 2010;Al Kaabi et al, 2011;Al Kaabi et al, 2012;Li et al, 2015). Hazard-based duration models have also the capability to account for spatial dependence of incident duration (Xie et al, 2015) and include random effects of explanatory variables (Tavassoli Hojati et al, 2014).…”
Section: Accident Durationmentioning
confidence: 97%
“…For example, Nam and Mannering (2000) adopted a two-year dataset from Washington State's IRT program, and developed models for the duration of each phase. Al Kaabi et al (2011) used a one-year dataset from Abu Dhabi's federal traffic statistics and collision reports to develop models specifically for the period of accident clearance; in a follow-up study, Al Kaabi et al (2012) studied the response time on Abu Dhabi's highways. Chung (2010) and Chung et al (2010) defined accident duration as the time between notification about an accident to its clearance, and developed models of the factors that significantly affect this duration.…”
Section: Accident Durationmentioning
confidence: 99%
See 1 more Smart Citation